Material Testing for The Development of Environmentally Friendly Concrete With Conventional Aggregate Substitutes - Kamil, Firmanilah; Purnomo, Julyan (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2024)
In Ketapang District, there is potential to reduce the environmental impact of concrete production by utilizing local agricultural waste. This study aims to determine the comparison between the physical properties of coconut fiber and palm kernel shells as aggregate substitutes in concrete, with the physical properties of conventional aggregates such as sand and crushed stone. Coconut coir came from tourism waste in Ketapang Regency, while palm kernel shells were taken from the waste of the local palm oil processing industry. Laboratory tests were conducted to compare the physical properties of coconut fiber and palm kernel shell with conventional aggregates, namely sand and crushed stone. The test results showed significant differences. Coconut husk had a specific gravity of 1.19 and palm kernel shell 1.59, compared to sand 2.09 and crushed stone 2.81. The moisture content of palm kernel shell (17.40%) was much higher than that of crushed stone (1.15%), while the water absorption of palm kernel shell reached 37.16%, far above the water absorption of crushed stone (4.05%). Coconut husk and palm kernel shell have lower specific gravity than conventional aggregates, making them ideal for lightweight concrete. However, the high water absorption of palm kernel shells requires adjustments to the concrete mix design. This study shows that the use of local waste materials can contribute to the development of environmentally friendly concrete, but careful composition control is required to maintain concrete performance. Keyword: aggregate, concrete, material testing.